Coping with paediatric referral—Ugandan parents’ experience - Peterson, Stefan; Sabiiti, Jesca Nsungwa; Were, Wilson; Nsabagasani, Xavier; Magumba, Godfrey; Nambooze, Josephine; Mukasa, Gelasius (The Lancet, 2004)
Referral of severely ill children to hospital is key in the Integrated Management of Childhood Illness (IMCI). In rural Uganda, we documented the caretakers' ability to complete referral to hospital from 12 health facilities. Of 227 children, only 63 (28%) had completed referral after 2 weeks, at a median cost of US$8.85 (range 0.40–89.00). Failure to attend hospital resulted from lack of money (139 children, 90%), transport problems (39, 26%), and responsibilities at home (26, 17%). Children with incomplete referral continued treatment at referring health centres (87, 54%) or in the private sector (45, 28%). Our results show that cost of referral must decrease to make paediatric referral realistic. When referral is difficult, more specific IMCI referral criteria should be used and first-level health workers should be empowered to manage severely ill children.